Potato mosaic viruses which infect plants of tuber-bearing Solanum spp. growing in the VIR field gene bank - E. V. Rogozina; N. V. Mironenko; N. A. Chalaya; Yu. Matsushita; H. Yanagisawa (Вавиловский журнал генетики и селекции)
Potato crop is particularly affected by virus diseases, and potato virus Y (PVY) currently considered the most important pathogen distributed worldwide as a diversity of strains. Wild and cultivated tuber-bearing species of the genus Solanum L., stored in the VIR collection, are used as the initial material in creation domestic potato varieties (Solanum tuberosum L.) resistant to virus diseases. The preservation and rational utilization of the potato collection is based on regular phytosanitary monitoring, including quarantine objects, foremost PSTVd (potato spindle tuber viroid). The aim of the work is to examine plants of tuber-bearing Solanum species in the field gene bank of VIR for the presence of PSTVd and PVX (potato virus X), PVS (potato virus S), PVM (potato virus M) and PVY, which are the most common viruses on potatoes in the North-West District of Russia. We examined clonal plants of 137 genotypes representing 31 species of the section Petota of the genus Solanum L. A diagnostic was carried out using ELISA, RT-PCR and indicator plants. No PSTVd was found in the studied plants, but a plural infestation by mosaic viruses was detected, more than half of the tested clones are infected with two or more viruses. In the studied samples, only 17 genotypes (12 %) are not infected by PVX, PVS, PVM and PVY according to the ELISA test. There are statistically significant differences in the virus infestation of Solanum species with different origins, according to Pearson’s chi-squared test. Among the studied genotypes of wild relatives of potatoes, the proportion of those affected by PVY was significantly higher in the South American than in the North American species (χ2 = 4.56, p = 0.03); the proportion of genotypes affected by PVХ was significantly higher in the North American species (χ2 = 8.81, p = 0.003), the critical value was χ2 = 3.841. PVY strains were identified by multiplex RT-PCR in 37 genotypes of Solanum spp. We found that 27 genotypes are infected by a common PVYO strain, two genotypes are infected by PVYNW (A) and PVYNW (B) strains, respectively, seven genotypes are infected by a mixture of PVYO +PVYNW (A) strains, and one is infected by a mixture of PVYO +PVYNTN-NW (SYRI)+SYRIII strains. The recombinant strains of PVY are detected in the North-West District of Russia for the first time. Coherency of the results of PVY strains detection by various (immunological, molecular and biological) methods is discussed.